Phytochemical composition and In-vitro activity of ethanolic extract of Eucalyptus globulus leaves against multidrug resistant poultry pathogens - Ullah, Assad; Anjum, Aftab Ahmad; Rabbani, Masood; Nawaz, Muhammad; Ashraf, Muhammad; Ijaz, Muhammad; Ali, Asad; Rashid, Anjum; Najeeb, Imran; Pervez, Asim (Cellular and Molecular Biology, 2021)
Aim of the present study was to determine the In-vitro antibacterial activity of ethanolic extract of E. globulus leaves against common multidrug resistant poultry pathogens. Phytochemical analysis through HPLC revealed that kaempeferol (7.315min) followed by querecetin (6.655min) and myrecetin (3.655min). Percent area of kaempeferol (6826.88%) was highest, followed by myrecetin (5516.22%) and querecetin (163.748%). Phytochemical investigation of ethanolic extract of E. globulus leaves through GCMS showed highest retention time (min) Î±-pinene (20.43) and Î±-terpineol (20.15) accompanied by spathulenol (11.97), piperitone (11.04). The ethanolic extracts of E. globulus leaves showed a highest zone of inhibition against S. pullorum SP6; 20.64± 2.08, E. coli SE 12; 19.75± 2.83, C. perfringens type A (CPM38-01); 19.46± 2.02. The highest level of MIC of E. globulus noted were against S. gallinarum S22; 133.37±53.294, S. gallinarum S1; 130.20±45.10, S. gallinarum S4; 129.47±24.182, S. gallinarum S3; 126.83±72.392. In conclusion, the study confirmed that the ethanolic extract of E. globulus is composed of active ingredients having antibacterial activity and can be referred as an alternate to antibiotics.